Klasyfikowanie pisma ręcznego według jego typu - Dzida, Jagoda (My University, 2022)
Głównym celem badawczym pracy było udzielenie odpowiedzi na pytanie, czy możliwe jest klasyfikowanie pisma ręcznego według jego typu (na podstawie jego cech graficznych), a jeśli tak - opracowanie takiej metody. W tym celu dokonano przeglądu literatury przedmiotu i przeprowadzono badania naukowe. Badania wykazały, że pewne cechy graficznie istotnie różnicują typy prób i że możliwe jest opracowanie metody klasyfikowania pisma ręcznego według typu. Opracowano 3 metody klasyfikowania i wykazano, że pozwalają one na skuteczne klasyfikowanie prób pisma ręcznego według typu.

The main aim of the dissertation was to answer the question if it is possible to classify handwriting samples as to their type (based on their graphic features) and if so – to find such a method of classification. In order to perform it, a review of the literature on the subject was done and scientific research was carried out. The results confirmed that some graphic features of the handwriting do differentiate the types of handwriting samples and that it is, indeed, possible to find a method of such a classification. During the research the 3 methods of classification were found and it was proved that they can be used to effectively classify the handwriting samples as to their type.
Classifying a handwriting sample as to its type
Wydział Prawa i Administracji
Keywords: pismo ręczne; badania klasyfikacyjne; próba pisma; typ próby; Handwriting; classification; handwriting sample; type of handwriting sample